High training/competition ratio, less incidence of injury? Professional football calendar exploration - Lacki, J. F. (Apunts Medicina de l'Esport, 2021)
Objectives: This study theorizes that a high training/competition ratio predisposes to fewer injuries in professional footballers. This has not been studied in elite professional players. The objective of this study was to investigate the incidence of injuries in professional players who had a frequency of one competition per week for twelve seasons. Furthermore, it highlights the importance of recovery-training cycles lasting from five to eight days between competitions. Method: This research is an analysis of prospectively recorded data on injuries in an Argentine professional football team. Data was collected throughout twelve seasons and on a daily basis. Results: The evaluated team had a frequency of 3.85 competitions per month and the ratio was 8.4 training hours per match hour throughout this twelve-year study. The injury incidence rate obtained in this investigation was 4.2 per 1000 training and competition hours. The injury incidence rate in training sessions was 2.3 injuries per 1000 training hours. The injury incidence rate in competition was 20.5 injuries per 1000 competition hours. Of 65% of all injuries, players returned to play (RTP) within seven days, with medical and kinesiological treatment customized for each athlete. Comparison tables with European Football are shown. Conclusions: Sports calendars with a high training/competence ratio and a recovery/training period lasting from 5 to 8 days between competitions could cause a decrease in injuries requiring longer RTP time and result in a relatively low injury incidence rate in professional footballers.